2016
DOI: 10.1002/acr.22765
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Baseline and Early Changes in C‐Reactive Protein and Interleukin‐6 Levels and Clinical Response to Tocilizumab in Rheumatoid Arthritis

Abstract: ObjectiveTo clarify the relevance of measuring interleukin‐6 (IL‐6) and C‐reactive protein (CRP) levels in order to predict clinical response to tocilizumab (TCZ) in rheumatoid arthritis patients.MethodsIn a pooled, post hoc analysis of 5 pivotal trials of TCZ, we examined the distributions of baseline serum concentrations of IL‐6 and CRP, stratified by randomized treatment group, and week 24 Disease Activity Score in 28 joints (DAS28) status (DAS28 <2.6 versus DAS28 ≥2.6). Relationships between early biomarke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 15 publications
5
22
0
Order By: Relevance
“…However, several studies have failed to identify the dominant cytokine in a specific individual with RA [ 21 ]. In this study, we found that the relative mRNA levels of IL-6 and TNF-α were inversely correlated in blood samples from 45 newly diagnosed RA patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several studies have failed to identify the dominant cytokine in a specific individual with RA [ 21 ]. In this study, we found that the relative mRNA levels of IL-6 and TNF-α were inversely correlated in blood samples from 45 newly diagnosed RA patients.…”
Section: Discussionmentioning
confidence: 99%
“…While Plt, Hb, AST, and ALT were correlated with TCZ efficacy, it was an interesting finding that C-reactive protein (CRP) was not correlated with the efficacy of TCZ, and this tendency was similar in the additional 228 patients (data not shown). Recently, it was reported that baseline serum concentration of CRP might not be predictive of clinical outcomes after TCZ treatment [ 21 ]. Although the reasons for this phenomenon are unclear, such acute inflammatory markers might not be suitable for prediction because of their dispersion.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, its effectiveness has been borne out in long-term extension studies tracking disease activity in >4000 patients 2,414244 . This is particularly true for disease activity measures that incorporate the CRP 45 , which may reflect blockade of IL-6 signaling 8,46 . Tofacitinib has also been effective in improving patient-reported outcomes 36,4748 and other disease measures that do not incorporate CRP 45 .…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…Calprotectin and CRP are different proteins, and thus the unit used to express their concentrations does not make them less or more comparable, as they are different means of inflammation. In rheumatology, biomarker research is a growing field, with many comparative studies focusing on the accuracy of CRP versus new biomarkers using different units (1,2). In fact, the pivotal studies that demonstrated that calprotectin more accurate-ly stratifies disease activity than CRP levels in juvenile idiopathic arthritis (3) and inflammatory bowel disease (4) used the same units we did.…”
Section: Replymentioning
confidence: 99%